Anxiety and depression among nurses working in a tertiary care hospital in South India - Shajan, Ashley; Nisha, Catherin (International Journal of Advances in Medicine, 2019)
Background: Nursing binds human society with a bond of care and affection. Nurses are often the first healthcare professional that patients meet. Quality of care for patients is strongly linked to the performance of the nursing staff. If the mental health status of these nurses is troubled, then they will not be able to give their full attention to this demanding task. Nowadays, all efforts to fight health workers’ illnesses are extremely important. This descriptive cross-sectional study will give us knowledge regarding the anxiety and depression status among nurses and give the nursing staff an opportunity to express their difficulty in professional life working in a tertiary care hospital in South India. Objective of this study was conducted to assess the prevalence of anxiety and depression among nurses working in a tertiary care hospital and to assess the correlation between various factors influencing the level of anxiety and depression among nurses. Methods: Nurses were selected by simple random sampling till the sample size was obtained. A standardised questionnaire was handed over to the participants to collect relevant data and was assessed by Hospital Anxiety and Depression Score (HADS) and analysed using SPSS software. Results: The participants consist of 120 nurses. The study gives frequencies of nurses with anxiety as 48(40%) and depression as 43(35.8%). There does not exist any significant correlation of anxiety and depression with various factors influencing them. Conclusions: Anxiety and depression levels are increased in the younger and less experienced nurses. Thereafter, interventions can be planned to improve the quality of work-life of nurses that can improve patient care and in turn benefit the society.